2009
DOI: 10.1177/039463200902200107
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Interleukin-2 Receptor as an Indicator of Immunological Disturbance Found in Silicosis Patients

Abstract: Silicosis patients (SILs) possess not only respiratory disorders but also alterations in autoimmunity. To determine an early indicator of immunological disturbance in SILs, the role of serum-soluble interleukin (IL)-2 receptor (sIL-2R) was analyzed. Often SILs, immunological clinical parameters such as immunoglobulin (Ig) G, complements, the titer of autoantibodies including anti-nuclear antibodies (ANA), anti-ScI-70 antibody (Ab) and anti-centromere (CM) Ab, and experimental indicators such as serum-soluble F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…Our studies corroborate this tendency and revealed that silicosis patients show higher titers of anti-nuclear antibodies (ANA) compared with that of healthy donors [21,22]. Furthermore, we discovered several specific autoantibodies in silicosis patients.…”
Section: Autoantibodies Detectedsupporting
confidence: 83%
See 2 more Smart Citations
“…Our studies corroborate this tendency and revealed that silicosis patients show higher titers of anti-nuclear antibodies (ANA) compared with that of healthy donors [21,22]. Furthermore, we discovered several specific autoantibodies in silicosis patients.…”
Section: Autoantibodies Detectedsupporting
confidence: 83%
“…Thus, we measured serum sIL-2R levels in cases of silicosis [22]. Our results showed that these levels tended to be higher than those of healthy donors and lower than those of SSc patients, but the differences between groups were not significant.…”
Section: Chronic Activation Of Responder T Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…2a). In addition, soluble IL-2 receptor (sIL-2R) was elevated in SIL serum when compared with that in HV [43]. Experimentally, silica particles activated freshly isolated peripheral T cells derived from HV monitored by the expression of CD69 on the surface [44].…”
Section: Effects On Nk Cellsmentioning
confidence: 99%
“…There is a known association between inhalational silica exposure and SSc and an entity linking SSc with exposure to silica particles, with or without the development of silicosis, is called the Erasmus syndrome [40]. Patients with silicosis in general are also noted to have alterations in immunity, with a recent article noting alterations in soluble interleukin 2 (sIL2) receptors in these patients [41]. The mechanisms for the biological effects of silica are still not fully understood.…”
Section: Pneumoconiosis (Silicosis)mentioning
confidence: 99%